Improving Students’ Problem Solving Skills and Laboratory Performance by Sublimation Apparatus Modification Project - Ulya, Haritsah; Fadiawati, Noor; Abdurrahman, Abdurrahman (Jurnal Pendidikan MIPA, 2022)
This study aims to develop a sublimation tool to improve problem solving skills and performance in the laboratory. The research method used is the Research and Development (R&D) method with a 4D model. The research sample consisted of control and experimental classes. The sampling technique used was purposive sampling. The results showed that the developed sublimation tool stated: (1) effective for use, it was obtained (1.64). In addition, the results of the development are also good in improving students' problem solving skills with n gain (0.64) with high criteria (2) the results of responses from students' responses to the attractiveness aspect (100%), readability aspect (96.29%), and tool design (100%). Based on the results of research and development, it can be stated that the developed sublimation tool is effective for improving problem solving skills and performance in the laboratory and can be used in practical experiments in studying the material for separating mixtures with sublimation techniques. Keywords: development, sublimation, problem solving. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp872-881